Meningkatkan Hasil Belajar Matematika Materi Rasio Trigonometri Pada Koordinat Kartesius Dan Sudut Relasi Trigonometri Pada Siswa Kelas X IPA-4 SMA Negeri 7 Palu Melalui Penerapan Metode Pembelajaran Cooperative Script - Nurhayatin Nurhayatin (MEDIA PERSPEKTIF : Journal of Technology, 2022)
Learning mathematics at SMA Negeri 7 Palu is generally dominated by teachers, causing low student learning outcomes. The purpose of this study was to improve the results of learning mathematics in the matter of trigonometry ratios in Cartesian coordinates and angles of trigonometric relations through the application of the cooperative script learning method. This research is a class action research (PTK) in class X IPA.4 SMA Negeri 7 Palu, totaling 32 students. This research was conducted in three cycles and data was collected through observation sheets from teacher activities and student activities, as well as action results tests. The results of the research on teacher and student activities increased from cycle I to cycle II and cycle III and were in the good and very good categories. Analysis of learning outcomes obtained from student data in cycles I, II and cycle III experienced an increase, the classical absorption value of cycle I (73.51%), and cycle II (74.59%) and cycle III (80.22%) as well as The classical completeness obtained from the data of students in cycle I, II and cycle III has increased, the classical absorption value of cycle I (59.38%), cycle II (71.88%) and cycle III (84.38%). Based on the indicators of the success of this study, if the percentage of classical absorption and classical mastery reaches 80%, it can be concluded that the application of the cooperative script learning method can improve mathematics learning outcomes in the matter of trigonometry ratios in Cartesian coordinates and angles of trigonometric relations in class X IPA.4 SMA Negeri 7 Palu.